Principles of Entrepreneurship (ENT530): Case Study: Company Analysis: Byhisdaisy Sdn.Bhd / Siti Hajar Binti Mohd Kamal … [et al.] - Mohd Kamal, Siti Hajar; Mohd Idrus, Siti Nur Aishah; Mohammed Salleh, Muhammad Najib; Zaharuddin, Muhammad Zahrul Zikri; Muhammad Yusuf Hiu, Muhammad Uzayr Hiu (2021)
Byhisdaisy is a business company that selling out for women's clothes. In specification is Byhisdaisy the company selling women clothes such as Traditional Kebaya. The company Byhisdaisy has been operating for 4 years. For 4 years, Byhisdaisy company specialist focusing on embroidery and not embroidery. Most of all, company Byhisdaisy provided a variety of Traditional Kebaya. It also had their main objective mission and vision. The mission of company Byhisdaisy wants to achieve is to deliver happiness to their customer from a good quality product provided by Byhisdaisy company. There had 3 vision which is to achieve RM5 million sales on 31 December 2025 and then company Byhisdaisy had 3 branches company for 5 years coming soon. They have a building that worth RM 1 million also in 2025 years. To this day Company, Byhisdaisy possess 12 employees and 3internship employee. According to Tuan Iran COO (Chief Operating Officer) that hold department on the right side company which is possess 6 parts of the business such as sales, packing, and operation. Tuan Iran scope will take care of the department on the right side that focusing on sales, packing, and operation. The scope of the COO (Chief Operating Officer) will make sure that the operation will be going smoothly. In the interview session, Byhisdaisy may be focusing they are provided a good quality product that can make their customer or client will happy about their product. However, during this pandemic people lost interest to buy new clothes, or even they lost interest in OOTD. In addition, Byhisdaisy tries their hard to find a good solution for their problem which is the company provided delivery services and produce a new product that clients and customers comfortable to dress in the house during the pandemic.